Inventarisasi Anggrek sebagai Acuan Ecological Intelligence - Tomi Hidayat; Pariyanto Pariyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to inventory orchids as a reference for ecological intelligence in Danau Dendam Tak Sudah (DDTS), Bengkulu City. The method used in this research is purposive random sampling. The results showed that the orchids found around DDTS Bengkulu City were Coelogyne pandurata, Coelogyne speciosa, Trichocentrum luridum, Phalaenopsis amabilis, Dendrobium antennatum, Grammatophyllum speciosum, Vanda hookeriana, Aerides odorata, Spathoglottis zurea. In conclusion, nine species of orchids were found belonging to one family, namely Orchidaceae. Keywords: Orchid, Danau Dendam Tak Sudah, Ecological Intelligence